Rapid screening and identification of phenolic antioxidants in Hydrocotyle sibthorpioides Lam. by UPLC–ESI-MS/MS. (15th July 2016) - Kumari, Sima; Elancheran, R.; Kotoky, Jibon; Devi, Rajlakshmi
Highlights: UPLC–MS/MS was used for the separation, and characterization of the phenolic compounds. In vitro antioxidant activities of HS, CA and AV extracts were investigated. The phenolic profile of HS, CA and AV extracts were determined. Abstract: The aim of the study was to identify the phenolic compounds present in Hydrocotyle sibthorpioides (HS), Centella asiatica (CA) and Amaranthus viridis (AV) extracts and investigate their respective antioxidant activities. Herein, an ultra-high pressure liquid chromatography–mass spectrometer (UPLC–MS/MS) analytical method has been developed for the separation, and systematic characterization of the phenolic compounds in HS, CA and AV extracts and was compared along with ten standard phenolic compounds. Additionally, in vitro antioxidant activity of the phenolic compounds was also determined. The HS extract revealed excellent antioxidant activity such as 1, 1-diphenyl-2-picrylhydrazyl radical scavenging activity (IC50  = 19.7 ± 1.2 μg/mL), total reduction capability (0.169 ± 0.003 at 100 μg/mL), nitric oxide radical scavenging activity (IC50  = 39.33 ± 3.2 μg/mL), metal chelating activity (IC50  = 56.51 ± 3.6 μg/mL) and inhibition of lipid peroxidation (IC50  = 12.34 ± 2.3 μg/mL) as compared to CA and AV extracts. Furthermore, catechin, epicatechin, quercetin and chlorogenic acid were found to be the major components responsible for the antioxidant activity of the HS extract as evidenced from UPLC–MS/MS. Taken together, this study demonstrates the promising antioxidant properties of the HS extract, which can further be utilized in various pharmaceutical, food, and agricultural applications.